Real options and institutions - Smit, Han; Pennings, Enrico; van Bekkum, Sjoerd (Journal of International Business Studies, 2017)
This article shows how growth options are affected by two types of external uncertainty: Transactional uncertainty that stems from institutional voids and increases transaction costs, and economic uncertainty that arises from the business environment. We theorize that these two types of uncertainty have opposing effects: A firm’s growth option value (proportional to firm value) is negatively associated with transactional uncertainty, but positively associated with economic uncertainty. In an empirical study, we directly compare firm-level growth option values across 34 countries and indeed find that economic uncertainty and various institutional measures for transactional uncertainty correlate in opposite directions with the value of growth opportunities. Interestingly, in countries with lower transactional uncertainty, the economic uncertainty in the business environment is more strongly related to proportional growth option value. The link between a country’s institutions and firms’ proportional growth options value is also moderated by firm size. The implication of our study is that institutions, such as property rights, business regulations, and contract enforcement are important preconditions for companies to appropriate growth option value under economic uncertainty. Our findings may help public policymakers in devising strategies for institutional development in their country, and corporate executives in assessing institutional factors when managing their company’s growth options.